Multi-objective optimization of distributed generation placement and sizing in active distribution networks considering harmonic distortion - Ton, Trieu Ngoc; Le, Phong Minh; Le, Tan Minh (International Journal of Electrical and Computer Engineering (IJECE), 2026)
This paper presents a multi-objective optimization model for optimal placement and sizing of inverter-based distributed generation (DG) units in active distribution power systems (DPS), considering their impact on harmonic distortion. The model simultaneously minimizes total power losses and total harmonic distortion (THD), ensuring compliance with IEEE 519 standards. To solve this problem, the reptile search algorithm (RUN) is applied and compared with three metaheuristic algorithms: multi-objective particle swarm optimization (MOPSO), multi-objective grey wolf optimizer (MOGWO), and multi-objective whale optimization algorithm (MOWOA). Simulation results on IEEE 33-bus and 69-bus systems show that reptile search algorithm (RUN) reduces power losses by up to 6.1% and THD by 21.7% compared to MOPSO. Moreover, the results confirm a strong correlation between DG output power and harmonic amplitudes, highlighting the importance of power quality aware DG planning.